2019
DOI: 10.1159/000507551
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Enzymatic Capacity of <b><i>Kluyveromyces marxianus</i></b> for the Synthesis of Esters

Abstract: Recently, biotechnological opportunities have been found in non-Saccharomyces yeasts because they possess metabolic characteristics that lead to the production of compounds of interest. It has been observed that Kluyveromyces marxianus has a great potential in the production of esters, which are aromatic compounds of industrial importance. The genetic bases that govern the synthesis of esters include a large group of enzymes, among which the most important are alcohol acetyl transferases (AATases) and esterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…1-Nonanol and 1-Propanol were correlated to fruity notes [51]. to the corresponding alcohols [44][45][46]. Overall, the level of ketones increased in both fermented samples (Figure 3).…”
Section: Volatilome Analysismentioning
confidence: 86%
See 1 more Smart Citation
“…1-Nonanol and 1-Propanol were correlated to fruity notes [51]. to the corresponding alcohols [44][45][46]. Overall, the level of ketones increased in both fermented samples (Figure 3).…”
Section: Volatilome Analysismentioning
confidence: 86%
“…The formation of ketones was likely due to the yeasts, especially methyl ketones which arise from incomplete β-oxidation of fatty acids [42,43]. Ketones may either be oxygenated to esters or be reduced to the corresponding alcohols [44][45][46]. Overall, the level of ketones increased in both fermented samples (Figure 3).…”
Section: Volatilome Analysismentioning
confidence: 97%
“…Interestingly, K. marxianus shows a great potential in the production of esters, which are key aromatic compounds in the food industry [5]. Ethyl acetate and other short-chain volatile esters are used as industrial solvents and perfume ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Three synthesis ways of ethyl acetate have been reported [7]: hemiacetal oxidation (spontaneous formation of hemiacetal from acetaldehyde and ethanol under the action of enzymatic oxidization), condensation of ethanol and acetyl-CoA, and esteri cation of acetate and ethanol (the reverse synthesis of ethyl acetate from ethanol and acetate). However, it is di cult to produce ethyl acetate through esteri cation of ethanol and acetate because the ester-hydrolyzing activity of esterase is much higher than its ester-synthesizing activity [5]. The previous report demonstrated that ethyl acetate synthesis was characterized by the direct utilization of ethanol as a substrate or the hemiacetal reaction between sugar and acetaldehyde [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation